2020
DOI: 10.1111/hepr.13573
|View full text |Cite
|
Sign up to set email alerts
|

High expression of a vascular stricture‐related marker is predictive of an early response to tolvaptan, and a low fractional excretion of sodium is predictive of a poor long‐term survival after tolvaptan administration for liver cirrhosis

Abstract: Tolvaptan is a newly available diuretic that has a specific function in water reabsorption inhibition. Given that spironolactone or furosemide induces the aggravation of cirrhotic hyponatremia and dehydration, tolvaptan affects the management strategy of liver cirrhosis. Representative predictive markers of its response include renal function-related markers such as urea nitrogen or creatinine. However, vascular function-related markers have not been well investigated. We investigated the effect of the vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Several studies have shown that the administration of tolvaptan had no effect on survival [57,80,81]. These studies showed prognostic factors, such as complications with HCC and low fractional excretion of sodium (FENa) [57], complications with HCC and Child-…”
Section: Long-term Survival After Tolvaptan Administrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that the administration of tolvaptan had no effect on survival [57,80,81]. These studies showed prognostic factors, such as complications with HCC and low fractional excretion of sodium (FENa) [57], complications with HCC and Child-…”
Section: Long-term Survival After Tolvaptan Administrationmentioning
confidence: 99%
“…A prospective multicenter non-interventional, post-marketing surveillance study of 340 Japanese patients showed that body weight reduction was predominant in younger patients with a preserved renal function with low creatinine levels and a high estimated glomerular filtration rate (eGFR) [ 53 ]. A preserved renal function, as reflected by the eGFR or creatinine level, was shown to be important in several other reports and should therefore be considered a crucial factor predicting the effect of tolvaptan [ 54 , 55 , 56 , 57 ]. While even in chronic kidney disease (CKD) patients (eGFR < 45 mL/min/1.73 m 2 ), urinary volume increased and body weight decreased; however, the effect was somewhat lower than in non-CKD patients [ 58 ].…”
Section: Management Of Ascitesmentioning
confidence: 99%
See 2 more Smart Citations